2017
DOI: 10.2987/16-6594.1
|View full text |Cite
|
Sign up to set email alerts
|

Field Evaluation of Indoor Thermal Fog and Ultra-Low Volume Applications For Control of Aedes aegypti in Thailand

Abstract: Efficacies of a handheld thermal fogger (Patriot™) and a backpack ultra-low volume (ULV) sprayer (Twister™) with combinations of 2 different adulticides (pyrethrin, deltamethrin) and an insect growth regulator (pyriproxyfen) were field-tested and compared for their impact on reducing indoor Aedes aegypti populations in Thailand. The effectiveness of the indoor space sprays was evaluated by sampling the natural Ae. aegypti population in houses and determining their physiological status, by monitoring mortality … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 20 publications
1
12
0
Order By: Relevance
“…Because individuals predominately (82%) rest within 1.5 m of the floor, and not necessarily on walls, IRS is not a suitable option for their control (Esu et al 2010, Manzanilla et al 2017). However, indoor ULV sprays have shown promise (Mani et al 2005, Harwood et al 2014, Ponlawat et al 2017) but are neither logistically suitable nor scalable for larger areas. With the adjustment of nozzle orientation and travel speed of truck-mounted ULV sprayers, complete mortality of caged female Ae.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because individuals predominately (82%) rest within 1.5 m of the floor, and not necessarily on walls, IRS is not a suitable option for their control (Esu et al 2010, Manzanilla et al 2017). However, indoor ULV sprays have shown promise (Mani et al 2005, Harwood et al 2014, Ponlawat et al 2017) but are neither logistically suitable nor scalable for larger areas. With the adjustment of nozzle orientation and travel speed of truck-mounted ULV sprayers, complete mortality of caged female Ae.…”
Section: Discussionmentioning
confidence: 99%
“…Another study on indoor application of ULD BP-300 and 9M Plus2 (deltamethrin) indicated that mortality of caged mosquitoes in the middle of a room ranged from 59% to 100% and 94% to 100% from thermal fog and ULV, respectively (Ponlawat et al 2017). Moreover, the mortality in cryptic areas (inside closed paper bags) ranged from 3% to 46% and 6% to 72% from thermal fog and ULV, respectively (Ponlawat et al 2017). Such applications, even with their promising efficacy, are limited in their utility to isolated homes and smaller communities due to time and personnel requirements.…”
Section: Introductionmentioning
confidence: 99%
“…In field trials in an earlier related study, even hand-fogging inside closed structures in Thailand did not provide100% control of sentinel adult Ae . aegypti placed in simulated refugia [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…• Use of PPF ultra low volume, thermal fogging, and fumigant technologies (15 studies) [67][68][69][70][71][72][73][74][75][76][77][78][79][80];…”
Section: Study Characteristicsmentioning
confidence: 99%
“…More recently, studies in Thailand and the USA have shown that multiple spraying machines using combinations of insecticides including PPF were unable to achieve high mortality among Aedes mosquitoes placed in hidden (protected) cages, and that the ULV sprays provided better emergence inhibition than the thermal foggers likely due to larger droplet size [70][71][72].…”
Section: Use Of Ppf Ultra-low Volume Spray Thermal Fogging and Fumimentioning
confidence: 99%